-6c+36=-42

Simple and best practice solution for -6c+36=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6c+36=-42 equation:



-6c+36=-42
We move all terms to the left:
-6c+36-(-42)=0
We add all the numbers together, and all the variables
-6c+78=0
We move all terms containing c to the left, all other terms to the right
-6c=-78
c=-78/-6
c=+13

See similar equations:

| 3u-2u+3u=20 | | 4a-7=1+5a | | 7x+10(2)=19x-50 | | 4x+24=6x+12 | | 4y+1=25+2y | | 2m+3m-m-2m=14 | | 3/4(8x−20)+12=4x+3 | | (u-5)=(u+5) | | 2m+3m−m−2m=14 | | 13p-7p+p-5p-p=13 | | 54=9+9y= | | -1=-6+c/2 | | (-2x)-x=9 | | v-2+5=(-1) | | a+1-5=(-8) | | 8+y=42/3 | | 13p−7p+p−5p−p=13 | | (-3n)-5n=0 | | 1+5b-4=(-18) | | 3m+4m=(-14) | | (-6n)-2n=0 | | -2(x-5)=3(-x+4 | | (-x)+6x=10 | | 3x^2+53x=-5 | | 16t-8t+t=18 | | 76=j-32 | | -47=-7(-8n-7)-8n | | 6s+4s+-4s-6s=12 | | 7^x=20.42 | | 5^(x+8)=25 | | -20=-4+r | | 2x^2+24x^2+64x=0 |

Equations solver categories